Support-free hollowing for 3D printing via Voronoi diagram of ellipses. (August 2018) - Lee, Mokwon; Fang, Qing; Cho, Youngsong; Ryu, Joonghyun; Liu, Ligang; Kim, Deok-Soo
Abstract: 3D printing, also called additive manufacturing, has been increasingly popular and printing efficiency has become more critical. To print artifacts faster with less material, thus leading to lighter and cheaper printed products, various types of void structureshave been designed and engineered inside of shape models. In this paper, we present a novel method for generating support-free elliptic hollowing for 3D shapes which can entirely avoid additional supporting structures. To achieve this, we perform the ellipse hollowing in one of the cross sectional polygons and then extrude the hollowed ellipses to the other parallel cross sections. To efficiently pack the ellipses in the polygon, we construct the Voronoi diagram of ellipses to reason the free-space around the ellipses and other geometric features by taking advantage of the available algorithm for the efficient and robust construction of the Voronoi diagram of circles. We demonstrate the effectiveness and feasibility of our proposed method by designing and printing support-free hollow for various 3D shapes usingPoretron, the program which computes the hollow by embedding appropriate APIs of the Voronoi Diagram Machine library that is freely available from Voronoi Diagram Research Center. It takes a 3D mesh model and produces an STL file which can be either fed into a 3D printer or postprocessed. Graphical abstract: Highlights: Support-free elliptic hollowing for 3D shapes via ellipse packing. Derivation of a class of support-free ellipses. Packing the support-free ellipses within a polygon (a cross-section of a 3D shape). Packing the ellipses within a polygon is solved very efficiently and precisely via Voronoi diagram.